Standoff Mid‐Infrared Emissive Imaging Spectroscopy for Identification and Mapping of Materials in Polychrome Objects. (27th December 2017) - Gabrieli, Francesca; Dooley, Kathryn A.; Zeibel, Jason G.; Howe, James D.; Delaney, John K.
Abstract: Microscale mid‐infrared (mid‐IR) imaging spectroscopy is used for the mapping of chemical functional groups. The extension to macroscale imaging requires that either the mid‐IR radiation reflected off or that emitted by the object be greater than the radiation from the thermal background. Reflectance spectra can be obtained using an active IR source to increase the amount of radiation reflected off the object, but rapid heating of greater than 4 °C can occur, which is a problem for paintings. Rather than using an active source, by placing a highly reflective tube between the painting and camera and introducing a low temperature source, thermal radiation from the room can be reduced, allowing the IR radiation emitted by the painting to dominate. Thus, emissivity spectra of the object can be recovered. Using this technique, mid‐IR emissivity image cubes of paintings were collected at high collection rates with a low‐noise, line‐scanning imaging spectrometer, which allowed pigments and paint binders to be identified and mapped.